Odpowiedzi

Najlepsza Odpowiedź!
2009-12-29T01:56:18+01:00
Wyznacz odleglosc punktu (3;-1;-1) od prostej przechodzacej przez pkt(0;2;1) oraz (-2;-1;-1)

(x-xa)/(xa-xb) = (y-ya)/(ya-yb)=(z-za)/(za-zb)

x/2 = (y-2)/(2+1) = (z-1)/(1+1)
x/2 = (y-2)/3 = (z-1)/2 /*6
3x=2(y-2)=3(z-1)
3x=2y-4=3z-3
2y-4-3x=3z-3
3y-4-3x-3z+3=0
-3x+3y-3z-1=0

A=-3
B=3
C=-3
D=-1

(3;-1;-1)
x₀=3
y₀=-1
z₀=-1

d=IAx₀+Bx₀+Cx₀+DI/√(A²+B²+C²)
d=I-3*3+3*(-1)-3*(-1)-1I/√((-3)²+3²+(-3)²)
d=I-9-3+3-1I/√(9+9+9)
d=I-10I/√(3*9)
d=10/(3√3) *√3/√3
d=10√3/9